Indirect Rotor Field Oriented Control of Induction Motor With Rotor Time Constant Estimation - Moh'd Radwan, Eyad Moh'd (2004)
This thesis presents an estimation technique of the inverse rotor time constant for Indirect Rotor Field Oriented Control (IRFOC) induction motor application. In this estimation technique two different equations are used to estimate the rotor flux in the stator reference frame. One of the equations is a function of the rotor time constant, rotor angular velocity and the stator currents, and the other equation is a function of measured stator currents and voltages. The equation that uses the voltage and the current signals of the stator serves as reference model, while the other equation works as an adjustable model with respect to the variation of the rotor time constant. Measurements of two phases of the current, and speed using an optical encoder are required in this estimation technique. The stator phase voltages are estimated from the DC bus voltage and the switching commands signals with compensation of the dead time effect. Field oriented control of induction motor is gaining wides acceptance in high performance AC motor drive applications. Field oriented control, in its both forms as a direct or indirect, gives the AC motor dynamics that are equivalent to that of a DC motor. However, direct and indirect field oriented control suffer from specific theoretical and practical problems. The approach of direct field oriented control with Hall sensors for flux sensing has limitations governed by the physical structure of the machine itself. On the other hand, the approach of indirect field oriented control of induction machines is highly dependent on the rotor parameters, which are not easily accessible for measurements except for the rotor speed. In a DC motor, spatial relationship of the torque and flux is maintained by the physical construction of the motor armature and field circuits. However, in an induction motor such spatial relationship does not maintain as such machine has usually a single terminal where electric power is supplied. Therefore, such relationship is maintained by external control methods. In a basic IRFOC of an induction motor, speed and phase currents are sensed in order to control the stator current vector such a way so it can be resolved into two components, one is to control the rotor flux and the other to control the motor torque. Successful decomposition of stator current vector into these two components requires the knowledge of the instantaneous position, of the rotor flux vector. Since the position of the rotor flux vector is estimated in an IRFOC scheme, and is dependent on the motor model (more specifically the rotor parameters), these parameters must be obtained accurately and match the motor parameters at all times. Unfortunately, rotor parameters vary and are not easily accessible for measurements. Therefore, this uncertainty about the rotor flux vector position degrades the dynamic operation of the drive.Enormous efforts have been made to improve IRFOC complicated hardware and software in order to coixpensate for such imperfection. Hence, this work focuses on the Indirect Rotor Field Oriented Control of induction motors with estimation of the rotor time constant. A simple yet effective rotor time constant identification method is presented and used for updating the slip calculator used by the IRFOC algorithms. A complete simulation model of an induction motor and IRFOC scheme is presented and tested using SIMULINWMATLAB, and experimentally implemented on a DSP Board (MCK243j without any need for voltage phase sensors. Simulation and experimental results were presented and compared to verify the validity of the proposed estimator for different operating conditions.